Best Answer

To find the answer, you need to first add negative one to the eleven on the other side of the equation. Now, you have the equation 5y= 3y+12. The next step is to subtract 3y from both sides. With the resulting equation, 2y=12, you need to divide both sides by 2. The answer is y=6. Algebra is nothing but combining like terms and using deductive reasoning to find a missing factor; keep working at it, and you'll be an expert!

Q: What does y equals in 5y-1 equals 3y plus 11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x-11

x = 5, y = -1

-2x plus 3y equals 1

2x + 3y = 11Subract 2x from each side:3y = 11 - 2xDivide both sides by 3:y = 11/3 - (2/3)x

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

Related questions

2x-11

How do you add 2x plus 3y equals 18 in 5x-y equals 11

(10,13)

Collect like terms: 2x + 3y + 3y - 5 - 6 2x + 6y - 11

(2,7)

x = 5, y = -1

5x+3y

4.34684352143

-2x plus 3y equals 1

y=-3-3 times -3= 9, 9+11= 20.-3y + 11 =20subtract 11 from each side, then -3y = 9divide each side by -3, then y = -3

The equation for 3y + 3y = -1 is 3y + 3y = -1.

1.67 or 1.667